Modification of Multi-walled Carbon Nanotubes with Nanoparticles for High Photocatalytic Activity - Tan, Tong Ling; Hamid, Sharifah Bee Abd; Lai, Chin Wei (Bentham Science Publishers, 2015)
Titanium dioxide (TiO2) nanoparticles were successfully attached to the outer surface of one dimensional oxidized multi-walled carbon nanotubes (MWCNTs) via sol-gel technique. It was well-established that calcination temperature played a critical role in controlling the crystallinity and phase of MWCNTs/TiO2composites. Thus, the effects of calcination temperature on the resulting MWCNTs/TiO2 were illustrated. The phase transition of MWCNTs/TiO2 composites was determined using XRD analysis. The photocatalytic activity evaluation of MWCNTs/TiO2 composites was conducted under degradation of organic dye (methyl orange solution). The results revealed that annealed MWCNTs/TiO2 composites showed significantly enhanced photocatalytic activity due to the highly crystalline anatase TiO2 structures.